Exploring the Impact of IT-Enabled Innovations on Athlete Performance: Insights from Rapid Product Development Research - Jimmy Abeza; Ellen Gretchen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study explores the revolutionary effects of IT-enabled innovations on athletic performance, utilizing knowledge from the vibrant field of research on fast product development. Sports have embraced a digital revolution that has transformed training, performance analysis, injury prevention, and fan involvement in an era where technology is developing at an unheard-of rate. With wearable technology and immersive virtual worlds, training approaches have undergone a paradigm change that benefits athlete today. These developments stretch the limits of human potential by allowing athletes to fine-tune their performances with unmatched accuracy. Data-driven insights have replaced subjective evaluations in performance analysis. Coaches may use advanced analytics, powered by machine learning, to improve player performance, create strategic game plans, and gain a competitive advantage. Additionally, IT-enabled innovations have changed how players, teams, and spectators interact. The spectator experience is improved with augmented reality overlays, and fan participation on social media and interactive platforms is increased regardless of a fan's location. Although these developments are revolutionary, moral issues are very important. Complex issues that must be resolved include preservation data privacy, maintaining fair competition, and establishing the limits of performance enhancement.